(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
These are experiences that took place in the course Cartographic and Performative Writing in Play, taught in the Postgraduate Programme in Performing Arts at the Unicamp Institute of Arts in the first semester of 2024. A spiral movement towards the materialities of the research was encouraged, exercising experimental writing. The pedagogical gestures of welcoming, sharing, peeking and tensing were activated, allowing the writing singularities to arise from the research objects. ‘Marks’ (Rolnik, 1993) and “glowing scenes” (Llansol, 2011) stood out as theoretical aspects, hybridised with orality. Performative writing manifested itself in the fragmentary as a legitimate writing format.